An Exploration of Young Childrens' Understandings of Genetics Concepts from Ontological and Epistemological Perspectives. - Venville, G.; Gribble, Susan; Donovan, J. (John Wiley and Sons Inc., 2005)
This research examined 9- to 15-year-old children's understandings about basic genetics concepts and how they integrated those understandings with their broader theories of biology. A cross-sectional case study method was used to explore the students' (n = 90) understandings of basic inheritance and molecular genetics concepts such as gene and DNA. Data were collected by interview and were analyzed quantitatively and qualitatively. A theoretical framework consisting of an ontological perspective and an epistemological perspective informed the data analysis. The results indicate that the majority of students had a theory of kinship because they could differentiate between socially and genetically inherited characteristics. While these students had heard of the concepts gene and DNA, a bona fide theory of genetics was elusive because they did not know where genes are or what they do. The discussion explores popular cultural origins of students' understandings and potential ontological and epistemological barriers to further learning about genetics.